2022
DOI: 10.3389/fmicb.2022.980251
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatoid fungi synergize attraction of the Eurasian spruce bark beetle, Ips typographus to its aggregation pheromone in field traps

Abstract: Eurasian spruce bark beetle, Ips typographus is a destructive pest of the Norway spruce (Picea abies). Recent outbreaks in Europe have been attributed to global warming and other anthropogenic impacts. Bark beetles are guided by multiple complex olfactory cues throughout their life cycle. Male-produced aggregation pheromones, comprising 2-methyl-3-buten-2-ol and cis-verbenol, have been identified as the most powerful attractants for dispersing conspecifics. In addition to host trees, bark beetles interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…typographus were more attracted at short range to a combination of the pheromone mixture plus fungal volatiles than to the pheromone mixture alone. Similarly, a recent study reported that the presence of fungal volatiles increased the attraction of dispersing beetles to their pheromones in the field compared to traps with pheromones only [ 72 ]. Oxygenated monoterpenes and other fungal volatiles could provide information about the presence of fungal symbionts, which promote the successful development of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…typographus were more attracted at short range to a combination of the pheromone mixture plus fungal volatiles than to the pheromone mixture alone. Similarly, a recent study reported that the presence of fungal volatiles increased the attraction of dispersing beetles to their pheromones in the field compared to traps with pheromones only [ 72 ]. Oxygenated monoterpenes and other fungal volatiles could provide information about the presence of fungal symbionts, which promote the successful development of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the fungal volatiles 2-phenylethyl acetate and 3-methyl-1-butyl acetate increased the attraction of D. frontalis to its pheromone blend [ 70 ]. Similarly, I. typographus utilizes the fungal volatile 2-methyl-3-buten-2-ol as aggregation pheromone [ 16 , 30 ]; other FVOCs released from the same fungal symbionts improved the attraction of I. typographus to its pheromone [ 18 , 38 ]. Furthermore, the walnut twig beetle, Pityophthorus juglandis , was attracted to the FVOCs produced by its primary bark fungi [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether FVOCs elicit behavioral responses in bark beetles should be verified in the field experiment. Nevertheless, FVOCs and oxygenated monoterpenes can be potential components in integrated pest management strategies to control the bark beetle population [ 15 , 18 , 71 ]. The potential tree resistance biomarkers we have identified in our study can be used in tree breeding through genomic approaches to generate more resistant trees to beetle-fungal attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we showed that female I. typographus were more attracted at short range to a combination of pheromone plus fungal volatiles than to pheromone alone. Similarly, a recent study reported that the presence of fungal volatiles increased the attraction of dispersing beetles to their pheromones in the field compared to traps with pheromones only [63]. Oxygenated monoterpenes and other fungal volatiles provide information about the presence of fungal symbionts, which promote the successful development of their offspring.…”
Section: Discussionmentioning
confidence: 99%